A phase 2 trial of the oral smoothened inhibitor glasdegib in refractory myelodysplastic syndromes (MDS). (June 2019) - Sallman, David A.; Komrokji, Rami S.; Sweet, Kendra L.; Mo, Qianxing; McGraw, Kathy L.; Duong, Vu H.; Zhang, Ling; Nardelli, Lisa Ann; Padron, Eric; List, Alan F.; Lancet, Jeffrey E.
Highlights: Glasdegib in HMA-refractory MDS and CMML has limited single-agent activity. 56% of heavily pretreated, primarily high-risk MDS patients had stable disease after glasdegib administration. Stable disease or better was an independent covariate for improved overall survival. Results support investigation of glasdegib in novel drug combinations. Abstract: Hypomethylating agent (HMA) failure myelodysplastic syndrome (MDS) patients have poor outcomes and urgent need for novel therapies. Hedgehog pathway signaling upregulation plays a central role in myeloid neoplasm pathogenesis and leukemia stem cell survival. We evaluated the efficacy and safety of the smoothened inhibitor glasdegib in HMA-failure MDS (n = 35, median age 73 years). According to the International Prognostic Scoring System and the MD Anderson Global Risk Model, 54% and 77% had higher risk disease, respectively. Overall response was 6% (n = 2), and best response was marrow complete remission with hematologic improvement in both patients. Median OS and median follow-up were 10.4 and 42.8 months, respectively. Drug response/stable disease (SD) resulted in better OS than treatment failure (20.6 [95% CI, 10.4-] vs 3.9 months [95% CI, 0.7–9.1]; P < .0001). Response/SD was confirmed to be an independent covariate for improved OS ( P  <  .0001). Grade 3 or higher infections occurred in 11% of patients (n = 4); non-hematologic toxicities were rare. Early mortality (< 30 days) occurred in 11% of patients (n = 4). Glasdegib was well tolerated among HMA-failure MDS patients, although single-agent activity was limited. SD or better resulted in notably superior OS. These results support further investigation of glasdegib, potentially in novel drug combinations, in MDS patients.